ANALISIS IMPLEMENTASI PATIENT SAFETY DENGAN KEPUASAN IBU MELAHIRKAN - Rora Aisyah Silvani; Solichatin; Setiawandari, Setiawandari (Jurnal Medicare, 2025)
Patient safety is an essential component of quality healthcare, particularly in midwifery services. This study analyzed the relationship between patient safety implementation and maternal satisfaction during childbirth at Independent Midwifery Practices (TPMB) in South Surabaya. Using a quantitative analytic design with a cross-sectional approach, data were collected from 25 midwives and 25 postpartum mothers through questionnaires and observation checklists. The results showed that patient safety implementation by midwives was categorized as good (60%) and moderate (40%). Meanwhile, the majority of mothers reported being dissatisfied (40%), with only 24% stating they were very satisfied. The Spearman Rank correlation test indicated a p-value of 0.000 (<0.05) and a correlation coefficient of 0.649, signifying a strong relationship between the two variables. In conclusion, the implementation of patient safety is significantly associated with maternal satisfaction. Improving communication quality, empathy, and a holistic approach from midwives is necessary to ensure a safe, comfortable, and satisfying childbirth experience.